Targeting the AtCWIN1 Gene to Explore the Role of Invertases in Sucrose Transport in Roots and during Botrytis cinerea Infection - Veillet, Florian; Gaillard, Cécile; Coutos-Thévenot, Pierre; La Camera, Sylvain (Frontiers in Plant Science, 2016)
Cell wall invertases (CWIN) cleave sucrose into glucose and fructose in the apoplast. CWINs are key regulators of carbon partitioning and source/sink relationships during growth, development and under biotic stresses. In this report, we monitored the expression/activity of Arabidopsis cell wall invertases in organs behaving as source, sink or subjected to a source/sink transition after infection with the necrotrophic fungus Botrytis cinerea. We showed that organs with different source/sink status displayed differential CWIN activities, depending on carbohydrate needs or availabilities in the surrounding environment, through a transcriptional and posttranslational regulation. Loss-of-function mutation of the Arabidopsis cell wall invertase 1 gene, AtCWIN1, showed that the corresponding protein was the main contributor to the apoplastic sucrose cleaving activity in both leaves and roots. The CWIN-deficient mutant cwin1-1 exhibited a reduced capacity to actively take up external sucrose in roots, indicating that this process is mainly dependent on the sucrolytic activity of AtCWIN1. Using T-DNA and CRISPR/Cas9 mutants impaired in hexose transport, we demonstrated that external sucrose is actively absorbed in the form of hexoses by a sugar/H+ symport system involving the coordinated activity of AtCWIN1 with several Sugar Transporter Proteins (STP) of the plasma membrane, i.e. STP1 and STP13. Part of external sucrose was imported without apoplastic cleavage into cwin1-1 seedling roots, highlighting an alternative AtCWIN1-independent pathway for the assimilation of external sucrose. Accordingly, we showed that several genes encoding sucrose transporters of the plasma membrane were expressed. We also detected transcript accumulation of vacuolar invertase (VIN)-encoding genes and high VIN activities. Upon infection, AtCWIN1 was responsible for all the Botrytis-induced apoplastic invertase activity. We detected a transcriptional activation of several AtSUC and AtVIN genes accompanied with an enhanced vacuolar invertase activity, suggesting that the AtCWIN1-independent pathway is efficient upon infection. In absence of AtCWIN1, we postulate that intracellular sucrose hydrolysis is sufficient to provide intracellular hexoses to maintain sugar homeostasis in host cells and to fuel plant defenses. Finally, we demonstrated that B. cinerea possesses its own functional sucrolytic machinery and hexose uptake system, and does not rely on the host apoplastic invertases.